Pengaruh Cash Ratio (CR), Debt To Equity Ratio (DER) dan Return On Asset (ROA) terhadap Price To Book Value (PBV) Pada PT Astra Internasional, Tbk Periode 2016-2025 - Randhy Agusentoso; Hasudungan Pangaribuan; Wahyu Andri Wibowo; Yeti Kusmawati (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines the effect of Cash Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA) on Price to Book Value (PBV) at PT Astra International Tbk during the 2016–2025 period. The background of this research is based on the importance of financial performance indicators in influencing company value, as reflected in PBV. Investors generally use liquidity, solvency, and profitability ratios as considerations in assessing company performance and investment prospects. Therefore, this study aims to analyze both partially and simultaneously the influence of CR, DER, and ROA on PBV. This research employed a quantitative approach with an associative research method. The population and sample consisted of the company’s financial statements, with 10 financial report data selected using purposive sampling techniques. The research data were obtained from the official website of PT Astra International Tbk. The data were processed using SPSS version 26 and analyzed through multiple linear regression analysis. The study concludes that firm value is influenced by a combination of liquidity, leverage, and profitability, with their joint effect being statistically significant. However, only leverage shows a meaningful individual contribution, while liquidity and profitability do not demonstrate significant partial impacts. This suggests that financing decisions play a more decisive role in shaping market valuation. The findings offer implications for improving financial strategy and investment assessment.